Preliminary Findings From the Hearing Assessment in Response to Noise Screener: A New Pediatric Tool for Measuring Speech Identification in Noise - Irwin, Julia; Sullivan, Jessica; Fernandes, Barbara; Lotto, Alyssa (Perspectives of the ASHA Special Interest Groups, 2023)
Purpose: As part of the development of a speech-in-noise screener, speech recognition was measured in quiet and in an interrupted noise for 59 children with typical development according to parent report. Method: There were 39 monolingual and 20 bilingual participants. A corpus of 107 words were presented by a male and female speaker and present in the following conditions: +3 dB signal-to- noise ratio (SNR), −3 dB SNR, and quiet. Results: The participants showed increasing difficulty with speech identification as the SNR decreased. Additionally, age-related differences in accuracy were observed at each noise level. Conclusion: Our findings provide preliminary support for the utility and efficacy of a speech-in-noise screener for use with children.
Keywords: SCSU-student; dept.psy

Social Environment Influences the Temporal Dynamics of Sneak-Spawning in a Fish with Alternative Reproductive Tactics - Kustra, Matthew C.; Stiver, Kelly A.; Marsh-Rollo, Susan; Hellmann, Jennifer K.; Alonzo, Suzanne H. (The American Naturalist, 2023)
Several predictions of sperm competition theory are not well supported empirically. One potential reason is that most current theory and empirical research ignore how the social environment influence the temporal dynamics of mating. We propose that understanding these dynamics is key to understanding sexual selection and improving the predictive power of theory. To demonstrate the importance of these dynamics, we quantify how males’ social role, interactions among males, and current social environment influence the timing of mating in Symphodus ocellatus, a species with three alternative male reproductive tactics. Nesting males spawn synchronously with females; sneakers and satellites sneak-spawn with some time delay. Satellites also cooperate with nesting males. We found that satellites have shorter sneak-spawning delays than sneakers, a benefit of their cooperation with nesting males. Sneak-spawning delays decreased with increasing nest activity for sneakers but not for satellites, suggesting that sneakers may benefit from increased sperm competition intensity. Current sperm competition models ignore this potential benefit, which may be why the prediction that males should decrease investment when sperm competition involves more than two males is not well supported. Our study provides insight into mechanisms that drive variation in the timing of spawning, which could explain mismatches between theoretical and empirical results.
Keywords: alternative mating tactics; cooperation; dept.psy; peer-reviewed; reproductive competition; sexual selection; sneak-spawning; sperm competition

Developmental Themes in the Narrative of Adults with Early International Experiences - Abe, Jo Ann A. (Journal of Adult Development, 2023)
This study extends research on adult narrative identity in two major ways. First, it focuses on Adult Third Culture Kids (ATCKs), which refer to individuals who spent a part of their early developmental years abroad. In spite of the fact that they are an important demographic to study in this rapidly globalizing world, they have tended to be neglected in the field of psychology. Second, this study incorporates the cutting-edge tools of automated language analysis to extract developmental themes from autobiographical narratives using a bottom-up exploratory approach, as well as to identify psychological patterns and processes associated with the themes. The participants (N = 350; 18–80 + years old) were recruited from an alumni office of an international school and asked to write a narrative about the impact their international experiences had on their development. The meaning extraction method (MEM) yielded four developmental themes, which were remarkably consistent with the recurring themes that emerge from past research on adult narrative identity as well as ATCKs: past focus, communion, agency, and global focus. These four developmental themes, in turn, showed theoretically coherent patterns of relations with the demographic variables, linguistic markers of psychological patterns and processes, as well as self-reports of dimensions of well-being.
Keywords: Adult third culture kids (ATCKs); LIWC; MEH; Meaning extraction method; Narrative identity; dept.psy; peer-reviewed

Event-Related Potentials in Assessing Visual Speech Cues in the Broader Autism Phenotype: Evidence from a Phonemic Restoration Paradigm - Harwood, Vanessa; Baron, Alisa; Kleinman, Daniel; Campanelli, Luca; Irwin, Julia; Landi, Nicole (Brain Sciences, 2023)
Audiovisual speech perception includes the simultaneous processing of auditory and visual speech. Deficits in audiovisual speech perception are reported in autistic individuals; however, less is known regarding audiovisual speech perception within the broader autism phenotype (BAP), which includes individuals with elevated, yet subclinical, levels of autistic traits. We investigate the neural indices of audiovisual speech perception in adults exhibiting a range of autism-like traits using event-related potentials (ERPs) in a phonemic restoration paradigm. In this paradigm, we consider conditions where speech articulators (mouth and jaw) are present (AV condition) and obscured by a pixelated mask (PX condition). These two face conditions were included in both passive (simply viewing a speaking face) and active (participants were required to press a button for a specific consonant–vowel stimulus) experiments. The results revealed an N100 ERP component which was present for all listening contexts and conditions; however, it was attenuated in the active AV condition where participants were able to view the speaker’s face, including the mouth and jaw. The P300 ERP component was present within the active experiment only, and significantly greater within the AV condition compared to the PX condition. This suggests increased neural effort for detecting deviant stimuli when visible articulation was present and visual influence on perception. Finally, the P300 response was negatively correlated with autism-like traits, suggesting that higher autistic traits were associated with generally smaller P300 responses in the active AV and PX conditions. The conclusions support the finding that atypical audiovisual processing may be characteristic of the BAP in adults.
1 citations (Crossref) [2023-10-31] Number: 7
Keywords: audiovisual; dept.psy; event-related potentials; peer-reviewed; phonemic restoration; speech perception

Neural and Behavioral Differences in Speech Perception for Children With Autism Spectrum Disorders Within an Audiovisual Context - Irwin, Julia; Harwood, Vanessa; Kleinman, Daniel; Baron, Alisa; Avery, Trey; Turcios, Jacqueline; Landi, Nicole (Journal of Speech, Language, and Hearing Research, 2023)
Purpose: Reduced use of visible articulatory information on a speaker's face has been implicated as a possible contributor to language deficits in autism spectrum disorders (ASD). We employ an audiovisual (AV) phonemic restoration paradigm to measure behavioral performance (button press) and event-related potentials (ERPs) of visual speech perception in children with ASD and their neurotypical peers to assess potential neural substrates that contribute to group differences. Method: Two sets of speech stimuli, /ba/–“/a/” (“/a/” was created from the /ba/ token by a reducing the initial consonant) and /ba/–/pa/, were presented within an auditory oddball paradigm to children aged 6–13 years with ASD (n = 17) and typical development (TD; n = 33) within two conditions. The AV condition contained a fully visible speaking face; the pixelated (PX) condition included a face, but the mouth and jaw were PX, removing all articulatory information. When articulatory features were present for the /ba/–“/a/” contrast, it was expected that the influence of the visual articulators would facilitate a phonemic restoration effect in which “/a/” would be perceived as /ba/. ERPs were recorded during the experiment while children were required to press a button for the deviant sound for both sets of speech contrasts within both conditions. Results: Button press data revealed that TD children were more accurate in discriminating between /ba/–“/a/” and /ba/–/pa/ contrasts in the PX condition relative to the ASD group. ERPs in response to the /ba/–/pa/ contrast within both AV and PX conditions differed between children with ASD and TD children (earlier P300 responses for children with ASD). Conclusion: Children with ASD differ in the underlying neural mechanisms responsible for speech processing compared with TD peers within an AV context.
0 citations (Crossref) [2023-10-31]
Keywords: dept.psy; peer-reviewed

Where on the face do we look during phonemic restoration: An eye-tracking study - Baron, Alisa; Harwood, Vanessa; Kleinman, Daniel; Campanelli, Luca; Molski, Joseph; Landi, Nicole; Irwin, Julia (Frontiers in Psychology, 2023)
Face to face communication typically involves audio and visual components to the speech signal. To examine the effect of task demands on gaze patterns in response to a speaking face, adults participated in two eye-tracking experiments with an audiovisual (articulatory information from the mouth was visible) and a pixelated condition (articulatory information was not visible). Further, task demands were manipulated by having listeners respond in a passive (no response) or an active (button press response) context. The active experiment required participants to discriminate between speech stimuli and was designed to mimic environmental situations which require one to use visual information to disambiguate the speaker’s message, simulating different listening conditions in real-world settings. Stimuli included a clear exemplar of the syllable /ba/ and a second exemplar in which the formant initial consonant was reduced creating an /a/−like consonant. Consistent with our hypothesis, results revealed that the greatest fixations to the mouth were present in the audiovisual active experiment and visual articulatory information led to a phonemic restoration effect for the /a/ speech token. In the pixelated condition, participants fixated on the eyes, and discrimination of the deviant token within the active experiment was significantly greater than the audiovisual condition. These results suggest that when required to disambiguate changes in speech, adults may look to the mouth for additional cues to support processing when it is available.
0 citations (Crossref) [2023-10-31]
Keywords: dept.psy; peer-reviewed

Motivation states to move, be physically active and sedentary vary like circadian rhythms and are associated with affect and arousal - Budnick, Christopher J.; Stults-Kolehmainen, Matthew; Dadina, Cyrus; Bartholomew, John B.; Boullosa, Daniel; Ash, Garret I.; Sinha, Rajita; Blacutt, Miguel; Haughton, Adrian; Lu, Tom (Frontiers in Sports and Active Living, 2023)
IntroductionMotivation to be physically active and sedentary is a transient state that varies in response to previous behavior. It is not known: (a) if motivational states vary from morning to evening, (b) if they are related to feeling states (arousal/hedonic tone), and (c) whether they predict current behavior and intentions. The primary purpose of this study was to determine if motivation states vary across the day and in what pattern. Thirty adults from the United States were recruited from Amazon MTurk.MethodsParticipants completed 6 identical online surveys each day for 8 days beginning after waking and every 2–3 h thereafter until bedtime. Participants completed: (a) the CRAVE scale (Right now version) to measure motivation states for Move and Rest, (b) Feeling Scale, (c) Felt Arousal Scale, and (d) surveys about current movement behavior (e.g., currently sitting, standing, laying down) and intentions for exercise and sleep. Of these, 21 participants (mean age 37.7 y; 52.4% female) had complete and valid data.ResultsVisual inspection of data determined that: a) motivation states varied widely across the day, and b) most participants had a single wave cycle each day. Hierarchical linear modelling revealed that there were significant linear and quadratic time trends for both Move and Rest. Move peaked near 1500 h when Rest was at its nadir. Cosinor analysis determined that the functional waveform was circadian for Move for 81% of participants and 62% for Rest. Pleasure/displeasure and arousal independently predicted motivation states (all p's < .001), but arousal had an association twice as large. Eating, exercise and sleep behaviors, especially those over 2 h before assessment, predicted current motivation states. Move-motivation predicted current body position (e.g., laying down, sitting, walking) and intentions for exercise and sleep more consistently than rest, with the strongest prediction of behaviors planned for the next 30 min.DiscussionWhile these data must be replicated with a larger sample, results suggest that motivation states to be active or sedentary have a circadian waveform for most people and influence future behavioral intentions. These novel results highlight the need to rethink the traditional approaches typically utilized to increase physical activity levels.
2 citations (Crossref) [2023-10-31]
Keywords: dept.psy; peer-reviewed

Qualitative and quantitative evidence of motivation states for physical activity, exercise and being sedentary from university student focus groups - Stults-Kolehmainen, Matthew A.; Gilson, Todd A.; SantaBarbara, Nicholas; McKee, Paul C.; Sinha, Rajita; Bartholomew, John B.; Boullosa, Daniel; Budnick, Christopher J.; Bueno, Fabio Amador; Haughton, Adrian; Barker, Jessica L.; Ash, Garrett I. (Frontiers in Sports and Active Living, 2023)
Motivation for physical activity and sedentary behaviors (e.g., desires, urges, wants, cravings) varies from moment to moment. According to the WANT model, these motivation states may be affectively-charged (e.g., felt as tension), particularly after periods of maximal exercise or extended rest. The purpose of this study was to examine postulates of the WANT model utilizing a mixed-methods approach. We hypothesized that: (1) qualitative evidence would emerge from interviews to support this model, and (2) motivation states would quantitatively change over the course of an interview period. Seventeen undergraduate students (mean age = 18.6y, 13 women) engaged in focus groups where 12 structured questions were presented. Participants completed the “right now” version of the CRAVE scale before and after interviews. Qualitative data were analyzed with content analysis. A total of 410 unique lower-order themes were classified and grouped into 43 higher order themes (HOTs). From HOTs, six super higher order themes (SHOTs) were designated: (1) wants and aversions, (2) change and stability, (3) autonomy and automaticity, (4) objectives and impulses, (5) restraining and propelling forces, and (6) stress and boredom. Participants stated that they experienced desires to move and rest, including during the interview, but these states changed rapidly and varied both randomly as well as systematically across periods of minutes to months. Some also described a total absence of desire or even aversion to move and rest. Of note, strong urges and cravings for movement, typically from conditions of deprivation (e.g., sudden withdrawal from exercise training) were associated with physical and mental manifestations, such as fidgeting and feeling restless. Urges were often consummated with behavior (e.g., exercise sessions, naps), which commonly resulted in satiation and subsequent drop in desire. Importantly, stress was frequently described as both an inhibitor and instigator of motivation states. CRAVE-Move increased pre-to-post interviews (p < .01). CRAVE-Rest demonstrated a trend to decline (p = .057). Overall, qualitative and quantitative data largely corroborated postulates of the WANT model, demonstrating that people experience wants and cravings to move and rest, and that these states appear to fluctuate significantly, especially in the context of stress, boredom, satiety, and deprivation.
2 citations (Crossref) [2023-10-31]
Keywords: dept.psy; peer-reviewed